A LONG TERM FOLLOW UP: MESH VERSUS MAYO’S REPAIR IN PARAUMBILICAL HERNIA - Abdul Qayoom Daudpoto; Shahid Mirani; Rafique Ahmed Memon et al. (Journal of University Medical & Dental College, 2013)
A Long Term Follow up: Mesh versus Mayo’s repair in Para-umbilical Hernia. ABSTRACT Objectives: To compare the results of Complication length of follow up and recurrence rate in between two groups of mesh repair and mayo’s repair in adult para-umlical hernia. Material and method: A comparative study is carried out in surgical unit 2 Department of surgery Ghulam Muhammad Maher Medical College Sukkur from Feb. 2008 to Jan 2010. Sixty eight patients were randomly assigned into 2 groups. Group A underwent onlay mesh repair while Mayo’s repair was used in group B patients. All patients having Para umbilical hernia having defect in linea Alba less than 2 cm, irreducible, incarcerated hernia were excluded. Median follow up was 30 months and data collected regarding to size of hernia, type of operation, complications, length of follow up and recurrence rate. Results: More than 60% were above the age of 41 year, male female ratio was 1:7, and supra umbilical swelling was common presentation in (72%). Post operative Complications reported 19.44% in group A and 9.32% in group B including recurrence. There was no significant difference at surgical site, in scar cosmetic results, abdominal wall discomfort during breathing and over all patient satisfaction between both groups. The recurrence rate was 2.7% in mesh repair and 9.3% in mayo’s repairs cases with 30 months median long term follow up. Conclusion: Even After Higher Complication rate, mesh repair is superior in terms of recurrence and under certain circumstances suture repair has place, insignificant infection rate less costly and simple.